Direct Conversion of Cord Blood CD34+ Cells Into Neural Stem Cells by OCT4. (13th May 2015) - Liao, Wenbin; Huang, Nick; Yu, Jingxia; Jares, Alexander; Yang, Jianchang; Zieve, Gary; Avila, Cecilia; Jiang, Xun; Zhang, Xiao-Bing; Ma, Yupo
Abstract: : Cellular reprogramming or conversion is a promising strategy to generate desired stem cell types from somatic cells. Neural stem cells (NSCs) have the potential to regenerate central nervous system tissue and repair damage in response to injury. However, NSCs are difficult to isolate from human tissues and expand in sufficient quantities for therapy. Here, we report a method to generate neural stem cells from cord blood CD34-positive cells by ectopic expression of OCT4 in a feeder-free system. The induced cells (iNSCs) show a characteristic NSC-like morphology and can be expanded in vitro for more than 20 passages. In addition, the iNSCs are positive for neural stem cell-specific markers such as Nestin and Musashi-1 and are similar in gene expression patterns to a human neural stem cell line. The iNSCs express distinct transcriptional factors for forebrain, hindbrain, and spinal cord regions. Upon differentiation, the iNSCs are able to commit into multilineage mature neural cells. Following in vivo introduction into NOD/SCID mice, iNSCs can survive and differentiate in the mouse brain 3 months post-transplantation. Alternatively, we were also able to derive iNSCs with an episomal vector expressing OCT4. Our results suggest a novel, efficient approach to generate neural precursor cells that can be potentially used in drug discovery or regenerative medicine for neurological disease and injury. Significance: This study describes a novel method to generate expandable induced neural stem cells from human cord blood cells in a feeder-free system by a single factor, OCT4. The data are promising for future applications that require the generation of large amounts of autologous neural stem cells in disease modeling and regenerative medicine. Abstract : This study describes a novel method to generate expandable induced neural stem cells from human cord blood cells in a feeder-free system by a single factor, OCT4. The results suggest a novel, efficient approach to generate neural precursor cells that can be potentially used in drug discovery or regenerative medicine for neurological disease and injury.